Report of the Working Group on Chemicals For 7th Five Year Plan 1985-86 to 1989-90 - Planning Commission (Planning Commission, 1985)
The Planning Commission had set up a Working Group on Chemicals in September 1983 under the Chairmanship of Secretary, Ministry of Chemicals and Fertilisers for the preparation of the Seventh Five Year Plan 1985-90. The composition and terms of reference of the Working Group is at Annexure ' I' .
Ministry of Chemicals and Fertilisers
Ministry of Chemicals and Fertilisers